2018
DOI: 10.14744/nci.2018.02222
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Nailfold Videocapillaroscopy findings in Type 2 Diabetic Patients with and without Diabetic Retinopathy

Abstract: OBJECTIVE: Diabetes mellitus (DM) is a chronic hyperglycemic state and is associated with microvascular structural alterations. This study aimed to investigate the diameters of capillary loops and morphostructural changes using nailfold video capillaroscopy (NVC) in patients with type 2 DM with and without diabetic retinopathy (DR). METHODS: This cross-sectional, single-center study was conducted in patients with type 2 DM who were followed in outpatient clinics of opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…This pathophysiological phenomenon generates crossing capillaries, one of the first signs of capillary adaptation. Another study confirmed an elevated frequency of branched/ramified capillaries and TOR in T2D 18 . As recently reviewed by Maldonado et al, 19 unusual nailfold capillaroscopic patterns (such as TOR, ECT, AVA, and BIZ) can also be identified in individuals with diabetes mellitus.…”
Section: Discussionsupporting
confidence: 56%
“…This pathophysiological phenomenon generates crossing capillaries, one of the first signs of capillary adaptation. Another study confirmed an elevated frequency of branched/ramified capillaries and TOR in T2D 18 . As recently reviewed by Maldonado et al, 19 unusual nailfold capillaroscopic patterns (such as TOR, ECT, AVA, and BIZ) can also be identified in individuals with diabetes mellitus.…”
Section: Discussionsupporting
confidence: 56%
“…This investigation tool can help study vasculature in relatively early stage of diabetes and have prospects for further study in dermopathy patients and associate findings with retinopathy. 27 Also, infrared thermography studies can be done to evaluate the difference in temperature in the lesion and normal skin as there is a probability that higher…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In addition, earlier studies have also shown significant changes of the NVC pattern in patients with diabetes mellitus. Indeed, it appears that NVC allows for the assessment of the advancement of microangiopathy in diabetes mellitus and that NVC also indicates the presence of other complications, e.g., retinopathy [ 41 , 46 , 47 ]. The NVC pattern may also be influenced by other traditional CVD risk factors, such as arterial hypertension or dyslipidemia [ 48 , 49 ], as well as sleep apnea [ 48 ] and lifestyle [ 50 ].…”
Section: Discussionmentioning
confidence: 99%